Outcomes After Operative Fixation of Vancouver B2 and B3 Type Periprosthetic Fractures. Issue 5 (May 2022) - Barghi, Ameen; Hanna, Philip; Merchan, Nelson; Lechtig, Aron; Haggerty, Christopher; Weaver, Michael J.; von Keudell, Arvind; Wixted, John; Appleton, Paul; Rodriguez, Edward
Abstract : Objectives: The incidence of periprosthetic femur fracture in the setting of total hip arthroplasty is steadily increasing. Although the traditional dogma is that loose femoral components must be revised, we propose that in a frail geriatric population, anatomic reduction and fixation of Vancouver B2 and B3 periprosthetic fracture variants can restore stem stability and provide similar outcomes as revision arthroplasty. Design: Retrospective cohort study. Setting: Level 1 trauma center, tertiary academic medical center. Patients/Participants: We identified 94 patients over 65 years of age with Vancouver B2 and B3 fractures sustained between 2005 and 2019. Intervention: Patients were treated by either open reduction and internal fixation (ORIF) or revision arthroplasty (RA) with or without fixation. Main Outcome Measurements: Outcomes were mortality, time to full weight-bearing after surgery, intraoperative estimated blood loss, perioperative complications, reoperation, subsidence rate, and Patient-Reported Outcomes Measurement Information System pain and physical function scores. Results: A total of 75 (79.8%) ORIF and 19 (20.2%) RA patients were reviewed. One-year mortality for our cohort was 26.3%, and there was no significant difference between groups. Mean time to weight bear and surgical complication rates were similar between groups. The ORIF group had a significantly shorter time to surgery than the RA group. The RA group had greater incidence and amount of subsidence as well as estimated blood loss than the ORIF group. Conclusions: In geriatric patients with Vancouver B2 and B3 type periprosthetic fractures with known loose stems, ORIF may offer a similarly safe method of treatment than revision arthroplasty. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.